Dylematy motywowania pracowników przedsiębiorstw przemysłowych - Ziółkowska, Wiesława (Wydział Prawa i Administracji UAM, 1989)
A set of instruments and undertakings contained in the implementation programme of the second stage of the economic reform creates a chance for the growth of enterprising and innovative activity of individuals and groups. However, there are no guarantees that it will be so. All the solutions will turn out efficient only to the extent to which the employees will have to use and implement them. The source of compulsion should lie in practical and consistent observance of the dependence between the quality of life and work. A main factor determining the improvement of living conditions of people must be the improvement of the quality of work, its productivity and efficiency, mostly in the socialized sector of economy. An efficient process of motivating should be treated as a conscious transformation of dependencies between needs and aspirations of people on the one hand and the quality of work on the other into their motivation to show rational attitudes and behaviours which would lead to the formation and implementation of common aims of an enterprise and its crew. Motivating conceived in the above way should: 1) be based on the formation and practical exploitation of supply-creating function of pay. The essence of that function can be reduced to making people materially interested in efficient work in the socialized sector, what in turn would result in the growth of quality and quantity of goods and services. The pay in the socialized sector should become a real economic category instead of its „embarrasing value" of today; 2) approach the problem in a complex way, considering it in its interrelations with and dependencies on other managerial functions in an enterprise, especially planning and organizational functions; 3) make a practical use of motivation aspects of socializing the management of production. The above conception differs radically from a traditional approach to motivation. To expose that difference one should say that the actual pay policy is dominated by income and social function of pay and corresponds with conceiving the economy as one big multifactory enterprise.
Dillemmas of motivating the employees of industrial enterprises